Levels of Statistical Use in Applied Linguistics Research Articles: From 1986 to 2015. Issue 1 (2nd January 2019) - Khany, Reza; Tazik, Khalil
Abstract: The main objective of this study is to assess the levels of statistical use (basic, intermediate, and advanced) in Applied Linguistics research articles over the past three decades (from 1986 to 2015). The corpus included 4079 quantitative and mixed-methods studies published in ten prominent journals of Applied Linguistics. The articles were analysed and the statistical techniques used were aggregated by two current writers and four PhD students in TEFL. Results showed that descriptive statistics (40.04%) were by far the most commonly used technique followed by one-way ANOVA (14.91%), t-test (10.15%), and Pearson correlation (8.76%). Regarding the sophistication level of statistical use, about 78.77% ( n = 4686) of the techniques were classified as basic, 14.49% ( n = 862) as intermediate, and 6.74% ( n = 401) as advanced . Clearly, most of the techniques were either basic or intermediate, with a significant higher percentage for the former. So, a person with basic knowledge of statistics could understand 69.03% of the papers published during 1986 to 2015. It is discussed that researchers should be updated on recent statistical knowledge if they wish to statistically comprehend research articles published in Applied Linguistics journals.